Fabrication and characterization of MR thin films using IBS system - Qian, Yin (2009)
Recently magnetoresistive films have received great attention because of their applications in magnetic recording. One of the most used materials is Permalloy(NiFe) film, since this material has the low coercivity, anisotropy field and magnetostriction. It is thought as the most preferred single layer material in this area. The ion beam sputtering system is thought as the ideal equipment for the investigation of the influence of deposition parameters on the thin film because it can independently control various parameters that may influence the film growth. These parameters include sputtering ion energy and density and bombardment ion energy and density.